Immerser system of bamboo crops for small and medium (2020)
With the objective of strengthen the agroindustry in the coffee region through bamboo as an emergent commercialization product, the industrial design uses the concept of applied technologies to become in a fundamental tool in the optimization of this productive process in the region, the treating of bamboo on salt pools was chosen as main process to step on giving a response to some issues as the welfare of the worker in the immersion and floating labor and methodologies that improve the quality of the product, this innovation solutions in the region show a true commitment with the environment, reflected since the construction of the design up to the implemented materials that are part of their life cycle features.